Pregnancy-specific Hypertensive Disease: knowledge of a group of pregnant women users of a Basic Health Unit (Research, Society and Development, 2022)
Pregnancy-Specific Hypertensive Disease (PSHD) is a multisystem disease that affects 5% to 17% of pregnancies, which causes several complications resulting in significant maternal and fetal morbidity and mortality. In this study, the objective identifying the knowledges related to PSHD, carried by pregnant women users of the Basic Health Unit (BHU) Cuiabá, located in the city of Joaquim Nabuco, in the state of Pernambuco. It’s about a descriptive search, cross-sectional study with a qualitative approach, occurred through interviews, in which 20 pregnant women participated. Among the pregnant women interviewed, there was an average age of approximately 26 years and a low level of education. They presented succinct knowledge, with short answers and a feeling of doubt when answering, with regard to only 04 pregnant women said they had been oriented about the disease in the prenatal period. Superficial results were noted in relation to the basic notions of this pathology by pregnant women, as well as the professional's performance in terms of health promotion.